2011
DOI: 10.1158/1078-0432.ccr-10-1931
|View full text |Cite
|
Sign up to set email alerts
|

Extent and Patterns ofMGMTPromoter Methylation in Glioblastoma- and Respective Glioblastoma-Derived Spheres

Abstract: Purpose: Quantitative methylation-specific tests suggest that not all cells in a glioblastoma with detectable promoter methylation of the O6-methylguanine DNA methyltransferase (MGMT) gene carry a methylated MGMT allele. This observation may indicate cell subpopulations with distinct MGMT status, raising the question of the clinically relevant cutoff of MGMT methylation therapy. Epigenetic silencing of the MGMT gene by promoter methylation blunts repair of O6-methyl guanine and has been shown to be a predictiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 35 publications
2
78
1
Order By: Relevance
“…However, it is still not completely clear yet how many and which particular CpG sites in the MGMT CGI have to be methylated in order to (i) cause transcriptional silencing in primary tumor cells and (ii) to demonstrate the best association with treatment outcome and patient survival. In fact, each diagnostic methylation-specific assay -whether qualitative, semi-quantitative or quantitative -interrogates distinct sets of CpG sites within the MGMT CGI [35,36] (Fig. 1).…”
Section: Regulation Of Expression and Function Of Mgmtmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is still not completely clear yet how many and which particular CpG sites in the MGMT CGI have to be methylated in order to (i) cause transcriptional silencing in primary tumor cells and (ii) to demonstrate the best association with treatment outcome and patient survival. In fact, each diagnostic methylation-specific assay -whether qualitative, semi-quantitative or quantitative -interrogates distinct sets of CpG sites within the MGMT CGI [35,36] (Fig. 1).…”
Section: Regulation Of Expression and Function Of Mgmtmentioning
confidence: 99%
“…SP1 [35] NFκB [36] CBP/p300 [37] AP1 [38] HIF1α [40] Promoter miR-181b [43,44], miR-181d [44], mir221/222 [45], miR-767-3p, miR-648 [42] + NDRG1 [42] mRNA protein *50% events (immature data) Abbreviations: Karnofsky Performance Status (KPS), radiotherapy (RT), O6-methylguanine DNA-methyltransferase (MGMT), temozolomide (TMZ), overall survival (OS)…”
Section: Fig 6 Pragmatic Approach To Mgmt Testingmentioning
confidence: 99%
“…The epigenetically silenced MGMT might be responsible for the resistance of GICs to temozolmide [38] due to MGMT's ability to reverse alkylation at the O 6 positon of guanine and neutralize the cytotoxicity of alkylating agents such as temozolmide [39] . In addition to glioma stem cells, enhanced DNA repair capacity was also found in other CSCs.…”
Section: Ddr In Cscsmentioning
confidence: 99%
“…It is worthy of note that the status of MGMT methylation can vary for a particular tumor. For example in glioblastoma patients, previous studies have reported rates of 24%,33%,34%,35%, 40%,45%,47.5%,53%,68%, and 70% for MGMT promoter methylation (Esteller et al, 2000;Hegi et al, 2004;Hegi et al, 2005;Brandes et al, 2008;Dunn et al, 2009;Costa et al, 2010;Rivera et al, 2010;Sciuscio et al, 2011;Havik et al, 2012;Tang et al, 2012). It is possible that variability in the rates of promoter-region gene hypermethylation in meningioma tumors may be influenced by race, high fat food diet, polymorphism, smoking, dietary variables, and other environmental exposures.…”
Section: Discussionmentioning
confidence: 99%